2011
DOI: 10.1007/s13209-011-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach to strategy-proofness for single-peaked preferences

Abstract: This article establishes versions of Moulin's (Public Choice 35:437-455, 1980) characterizations of various classes of strategy-proof social choice functions when the domain consists of all profiles of single-peaked preferences on an arbitrary subset of the real line. Two results are established that show that the median of 2n + 1 numbers can be expressed using a combination of minimization and maximization operations applied to subsets of these numbers when either these subsets or the numbers themselves are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Corollary 4.1 (Moulin (1980), Weymark (2011)). Let S i be the maximal set of single-peaked preferences for all i ∈ N. Then, an SCF f : S N → X is unanimous and strategy-proof if and only if it is a min-max rule.…”
Section: X 2 X 2 X 2 X 2 X 3 X 3 X 3 X 3 X 4 X 4 X 5 X 2 X 1 X 3 mentioning
confidence: 95%
See 2 more Smart Citations
“…Corollary 4.1 (Moulin (1980), Weymark (2011)). Let S i be the maximal set of single-peaked preferences for all i ∈ N. Then, an SCF f : S N → X is unanimous and strategy-proof if and only if it is a min-max rule.…”
Section: X 2 X 2 X 2 X 2 X 3 X 3 X 3 X 3 X 4 X 4 X 5 X 2 X 1 X 3 mentioning
confidence: 95%
“…The study of single-peaked domains dates back to Black (1948), where it is shown that the pairwise majority rule is strategy-proof on such domains. Later, Moulin (1980) and Weymark (2011) characterize the unanimous and strategy-proof SCFs on these domains. 1,2 However, their characterization rests upon the assumption that the set of admissible preferences of each agent in the society is the maximal single-peaked domain, i.e., it contains all single-peaked preferences with respect to a given prior order over the alternatives.…”
Section: Motivation and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Moulin (1980), Barberà et al (1993) and Weymark (2011) characterize the unanimous and strategy-proof SCFs on the single-peaked domains as min-max rules. Peremans and Storcken (1999) and Manjunath (2014) characterize the unanimous and strategy-proof SCFs on the single-dipped domains as voting by extended committees.…”
Section: Our Contributionmentioning
confidence: 99%
“…Though Lemmas 3.12 and 3.13 use same techniques used in[Moulin, 1980] and[Weymark, 2011], we present them here for the sake of completeness.…”
mentioning
confidence: 99%